INTERNATIONAL BEST PRACTICES IN INTERREGIONAL AND INTERSECTORAL CLUSTER PARTNERSHIP DEVELOPMENT PATTERNS - Шкода, Мар’яна С. (Journal of Strategic Economic Research, 2023)
This study discusses international best practices in developing interregional and intersectoral cluster partnerships. It is observed that almost all developed economies, in particular, the countries of Western Europe, the USA and Japan adhere to strategies of cluster innovative development based on socioeconomic evolution through building competitive market economy. Successful cluster development practices in the European Union demonstrate that boosting cluster partnerships is of a primary significance to the European Commission that considers clusters as a powerful tool in eliminating economic disparities to ensure sustainable industry structural development, thus contributing to enhancing the competitiveness of the European economy. According to the research findings, cluster partnerships represented mostly by large business companies form essential part of the European industrial landscape, however, these clusters also include a range of other important actors of the industrial ecosystem, such as research institutions, science and technology parks, financial service providers, non-commercial organizations, etc. This study suggests that the European Union’s organizational model of cluster partnerships could be implemented as an adaptive framework which covers the following universal structural elements: the project coordinator which can be represented by a regional or national government authority or agency (defined as the "host organization") and project partners – the host cluster and at least two cluster or network organizations. Based on the Global Innovation Index 2020 data, the paper presents the results of calculations and substantiation on the degree of Ukraine’s innovation development (ranked 45, respectively), however, it reports of the insignificant level of cluster concentration to the overall innovation development in Ukraine (0.26) compared to global leaders, the integral indicator according to the Global Innovation Index is 2.86 (7 – max). It is argued that in modern methodology (in particular, in the framework of the Global Innovation Index); the level of cluster development is a critical element of the indicator for innovation-driven interaction, along with other variables that reflect the maturity of cluster development in the national economy.